Upper elementary students’ self-efficacy, affect, and avoidance associated with multisyllabic words: an exploratory study - Traga Philippakos, Zoi A.; Quinn, Margaret; Davis, Adalea (Frontiers in Psychology, 2025)
IntroductionThe purpose of this study was to develop and validate a questionnaire that addressed reading and spelling of big words to understand upper elementary learners’ perceptions of their abilities and challenges in relation to multisyllabic words.MethodsThe development of this questionnaire was part of a larger research project that aimed to develop instructional resources for upper elementary learners. Participants were 108 students across grades 3 to 5.ResultsThe results of an Exploratory Factor Analysis (EFA) found three factors that addressed self-efficacy for processes and tasks, affect, and avoidance. All factors correlated with reading measures with the exception of avoidance. Further, differences on self-efficacy and affect were found between the lower and low-average reading group. Finally, growth was found on self-efficacy and affect toward reading of big words as a result of instruction. Limitations and implications are discussed.